Government Communication Management in Handling Public Complaints Within the CRM Program at the Department of Communication Informatics and Statistics of DKI Jakarta Province - Demaisi, Silvia; Eva Eviany, Megandaru Widhi Kawuryan, , (Jurnal Mirai Management, 2024)
ABSTRACT The DKI Jakarta Provincial Government has implemented a CRM program for handling public complaints, as outlined in Governor Regulation Number 128 of 2017, which was amended by Governor Regulation Number 39 of 2019. Unfortunately, the program has not been well socialized to the public. Based on this background, this study analyzes the government communication management in handling public complaints within the CRM Program at the Department of Communication, Informatics, and Statistics, DKI Jakarta Province. We employed a qualitative descriptive method. Data collection techniques were conducted using purposive sampling with a snowball approach. In analyzing government communication management, we applied the four-step model theory by Cutlip, Center, and Broom (2013) to address the research problem. For primary data collection, we conducted field observations and interviews with informants from the Department of Communication, Informatics, and Statistics, DKI Jakarta Province, as well as the Jakarta Provincial Government Bureau. Additionally, we interviewed community informants (RW.08 Kebayoran Lama) as part of a triangulation process. This study concluded that the communication management in handling public complaints within the CRM program is generally quite effective. However, in the dimension of evaluation of complaint handling, the CRM program faces certain obstacles that need to be addressed. To overcome these obstacles, three strategies can be implemented: strengthening the commitment of leaders, conducting periodic socialization of the CRM program to the community, and continuously optimizing the system and improving CRM features. Keywords: Government Communication Management, CRM.